Anatomia visceral comparada de seis espécies de Amphisbaenidae (Squamata: Amphisbaenia) - Navega-Gonçalves,Maria Eliana C. (2009)
Visceral anatomy of amphisbaenids Amphisbaena vermicularis Wagler, 1824; Anops kingii Bell, 1833; Aulura anomala Barbour, 1914; Bronia bedai Vanzolini, 1991; Cercolophia cuiabana Strüssmann & Carvalho, 2001, and Leposternon microcephalum Wagler, 1824 were comparatively described and the size and the position of the organs in the pleuroperitoneal cavity was established in relation to the ventral scutellation. The main results were: the right lung presents different degrees of size reduction compared to the left lung, being conspicuous only in A. anomala, and L. microcephalum; the limit between small and large intestines is clear due to the presence of a caecum; the right lobe of the liver is larger than the left one, but its length varies within the same species and among species; the right gonad occupies a more cranial position in relation to the left one, in all six studied species; the right ovary is also larger than the left one in all studied specimens, whereas the left testicle can be larger or of the same size as the right one in some specimens; the shape of the testicles varies from elongated, kidney-shaped or oval; kidneys are symmetrically positioned at the caudal portion of the pleuroperitoneal cavity and one kidney can be larger than the other.